2014
DOI: 10.2807/1560-7917.es2014.19.28.20853
|View full text |Cite
|
Sign up to set email alerts
|

Cases of chikungunya virus infection in travellers returning to Spain from Haiti or Dominican Republic, April-June 2014

Abstract: Ten cases of chikungunya were diagnosed in Spanish travellers returning from Haiti (n=2), the Dominican Republic (n=7) or from both countries (n=1) between April and June 2014. These cases remind clinicians to consider chikungunya in European travellers presenting with febrile illness and arthralgia, who are returning from the Caribbean region and Central America, particularly from Haiti and the Dominican Republic. The presence of Aedes albopictus together with viraemic patients could potentially lead to autoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Moreover, all four known DENV genotypes were detected. An increase in imported CHIKV cases was also observed, as already documented in Spain, mainland France, and Northern Italy, along with the first identification of ZIKV imported cases; both findings are attributable to the recent dramatic spread of both CHIKV and ZIKV in previously unaffected areas [27, 4244]. The continuous expansion of the areas with Arbovirus circulation, together with the dispersion of Aedes mosquitoes spp.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, all four known DENV genotypes were detected. An increase in imported CHIKV cases was also observed, as already documented in Spain, mainland France, and Northern Italy, along with the first identification of ZIKV imported cases; both findings are attributable to the recent dramatic spread of both CHIKV and ZIKV in previously unaffected areas [27, 4244]. The continuous expansion of the areas with Arbovirus circulation, together with the dispersion of Aedes mosquitoes spp.…”
Section: Discussionmentioning
confidence: 57%
“…As of February 27, 2015, almost 964,341 probable and confirmed cases have been reported in the Caribbean and the rest of the Americas, including 183 deaths . During the past year, several European countries (France, Greece, Italy, the Netherlands, Spain, and Switzerland) have reported imported cases of CHIKV infection in patients with a travel history to the affected areas ; on October 2014, 11 locally acquired infections were reported from the Montpellier area in France . As of May 31, 2014, 10 imported chikungunya cases were reported in Italy, 8 of which were returning travelers from the Caribbean .…”
mentioning
confidence: 99%
“…Indeed, some authors have suggested that emerging arboviral diseases probably have a greater potential to spread in tropical or subtropical ecosystems [30]. The increasing number of chikungunya cases ever seen in Spain during the Caribbean outbreak also would reflect this fact and can be argued in support of the hypothesis [31].…”
Section: Discussionmentioning
confidence: 95%